Atmospheric Metal Constituent, Concentration and Health Impacts in the Urban Environment of Faisalabad (Pakistan) - Muhammad Attique Khan Shahid; Khadim Hussain; Maryam Saeed Awan (Journal of Basic & Applied Sciences, 2012)
Currently rapidly growing heavy metal pollution is a burning issue due to deteriorating air quality and health status of the inhabitants of the world. In the present study heavy metals in the solid aerosols as well as in the human blood samples from randomly selected sites related to Faisalabad environment were estimated using Atomic absorption spectrophotometry (AAS). The order of concentration of these toxic metals were found to be Zn>Cu>Cr>Ni>Pb>Cd for solid aerosols while Cu>Zn>Pb>Ni>Cr>Cd for blood samples. Overall effect of all these elements present in solid aerosols and blood samples is 22.5 % and 23.11% respectively. The contribution of different kinds of industries is the major source of emission of these elements in the environment. From where these enter in the food web and food chain when deposited on land or inhaled by the inhabitants of the area concerned. Concentration factor and Pollution load index (PLI) were also calculated which showed the shifting of Cd, Cu, Zn, Cr and Ni from solid aerosols to human blood causing severe health hazards while Pb was the only element found in blood which has its origin other than solid aerosols. This state of affairs shows that atmosphere of Faisalabad has worsened to an extent that protective measures are urgently required to overcome the health hazards generated by these potentially toxic pollutants.